THE RELATIONSHIP OF AUTOCAMIONES AEROCOCCUS VIRIDANS WITH REPRE-SENTATIVES OF THE NORMAL INTESTINAL FLORA OF LABORATORY ANIMALS - Степанський, Д.О.; Kremenchug, G..; Кошова, І.П. (World of Medicine and Biology, 2016)
Modern probiotics must possess antagonistic effect on pathogenic and conditionally pathogenic flora without affecting indigenous flora. The growing popularity of the use of personalized therapy autostable probiotic bacteria. The work studied the effect of selected homologous aurococcus-autocamiones the representatives of the normal microflora of mice when administered orally. Mice daily for 10 days in the morning on an empty stomach fed through a tube viridans167 A. and A. viridans 5м2015 (10 billion species on 1 reception). It is established that the microbial landscape of the intestine of mice before feeding aurococcus was varied and consisted of aerobic and anaerobic representatives, as well as Candida. Museum and symbiotic strains in a dosage of 10 billion / ml per os did not okazyvali antagonistic effect on normal microflora, which is presented in the intestine of mice in large numbers (anaerobes, bifidobacteria, lactobacilli). It was marked antagonistic activity against staphylococci, Candida, and Proteus. Also noted that autoimminity A. viridans 5м2015 okazyvali has greater antagonistic effect against the pathogenic flora.
Keywords: autoimminity; Aerococcus viridans; the normal microflora